Christian Apologists and the Antonine Emperors - Jones, Christopher P. (ARYS. Antigüedad: Religiones y Sociedades, 2019)
The Antonine period from Hadrian onwards sees the beginning of a Christian literature of “apology,” more precisely of defense and justification of the new religion. These defenses sometimes take the form of attacks on “pagan” cults or on Judaism. The Christians begin to represent their religion as a philosophy, worthy of consideration beside the traditional philosophies of the Graeco-Roman world. At the same time Christians are still persecuted, and imperial policy towards them, as expressed in the form of imperial edicts or implicitly by the practice of governors, continues, even if unevenly. There is a sharp upturn of persecution in the reign of Marcus Aurelius, perhaps exacerbated by the internal and external setbacks of the reign.
Keywords: Apology; martyrdom; Marcus Aurelius; persecution; philosophy